Factors Contributing to Brain Drain and Strategies for Retaining Skilled Professionals in Afghanistan: A Multisectoral Approach (Salam International Academic Journal, 2025)
This qualitative study investigates the underlying factors contributing to brain drain in Afghanistan and proposes actionable strategies to retain skilled professionals. Drawing on in-depth interviews with 33 Afghan professionals residing in various countries, the research identifies key drivers of emigration, including political instability, poor quality of life, ethnic discrimination, economic hardship, personal insecurity, lack of professional growth, and an uncertain future. Participants’ narratives reveal the multidimensional nature of intellectual migration and highlight the urgent need for systemic reforms. Proposed retention strategies include enhancing political stability and governance, improving public services and infrastructure, enforcing anti-discrimination measures, creating economic and employment opportunities, and engaging the Afghan diaspora. The findings underscore the importance of a holistic, multi-sectoral approach to mitigating brain drain and fostering an environment conducive to personal and professional fulfillment. This study offers practical insights for policymakers, development practitioners, and scholars aiming to strengthen Afghanistan’s human capital base and support long-term national development.
Keywords: Brain drain; skilled migration; Afghanistan; Political instability; Economic constraints; Diaspora engagement; Retention strategies; Professional development; Qualitative research